ChemInform Abstract: Recent Advances in the Chemistry of 1, 2, 4‐Oxadiazoles. Issue 44 (13th October 2016) - Pace, Andrea; Buscemi, Silvestre; Piccionello, Antonio Palumbo; Pibiri, Ivana
Abstract: Review: application of 1, 2, 4‐oxadiazoles in materials science and medicinal chemistry; 142 refs.